Diuron degradation using three-dimensional electro-peroxone (3D/E-peroxone) process in the presence of TiO2/GAC: Application for real wastewater and optimization using RSM-CCD and ANN-GA approaches. (March 2021) - Asgari, Ghorban; Seid-mohammadi, Abdolmotaleb; Rahmani, Alireza; Samadi, Mohammad Taghi; Salari, Mehdi; Alizadeh, Saber; Nematollahi, Davood
Abstract: The present study investigates the efficiency of a three-dimensional electro-peroxone (3D/E-peroxone) reactor filled with TiO2 -GAC in removing diuron from aqueous solution and in the remediation of real pesticide wastewater. The behavior of the system in terms of the effect of independent variables on diuron was investigated and optimized by RSM-CCD and ANN-GA methods. Both approaches proved to have a very good performance in the modeling of the process and determined the optimum condition of the independent variables as follows: initial pH = 10, applied current = 500 mA, supporting electrolyte = 0.07 M, ozone concentration = 10 mg L −1, and reaction time = 10 min. The 3D/E-peroxone process achieved a synergistic effect in diuron abatement and reduced significantly energy consumption, as compared to its individual components. H2 O2 concentration generated in the electrolysis system was notably increased in the presence of TiO2 -GAC microparticles. The BOD5 /COD ratio of the real pesticide wastewater increased from 0.049 to 0.571 within 90 min treatment. Giving to the considerable enhancement of the biodegradability of the wastewater, this study strongly suggests that the 3D/E-peroxone process can be considered as a promising pretreatment step before a biological treatment process to produce intermediates which are more easily degradable by microorganisms. Graphical abstract: Image 1 Highlights: TiO2 -GAC was used as particle electrodes in 3D/E-peroxone treatment of diuron. The 3D/E-peroxone system was optimized using RSM-CCD and ANN-GA approaches. H2 O2 produced in the system was increased in the presence of TiO2 -GAC microelectrodes. A pronounced synergistic effect was achieved in the 3D/E-peroxone process. The considerably enhanced biodegradability of real wastewater in the 3D/E-peroxone system.